2020
DOI: 10.1101/2020.10.16.20212480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Informal coercion during childbirth: risk factors and prevalence estimates from a nationwide survey among women in Switzerland

Abstract: Background In many countries, the increase in facility births is accompanied by a high rate of obstetric interventions. Lower birthrates or elevated risk factors such as women's higher age at childbirth and thus a higher need for control and security cannot entirely explain this rise in obstetric interventions. Another potential factor is that women feel coerced to agree to interventions; however, the prevalence of coercive interventions is unknown. Methods In a nationwide cross-sectional online survey, we as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Related to this, a recent nationwide Swiss study revealed that 26.7% of women experienced informal coercion in childbirth (i.e. opposition, intimidation, manipulation) and that the likelihood of experiencing informal coercion was higher (a) for in-hospitals births than for births in birth centers, (b) for women with a higher preference for autonomous decisions, and (c) for births with interventions [ 46 ]. Moreover, findings from the US found higher rates of mistreatment in hospital settings than in community birth settings such as birth centers and when women’s and providers’ preferences for care did not match one another [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Related to this, a recent nationwide Swiss study revealed that 26.7% of women experienced informal coercion in childbirth (i.e. opposition, intimidation, manipulation) and that the likelihood of experiencing informal coercion was higher (a) for in-hospitals births than for births in birth centers, (b) for women with a higher preference for autonomous decisions, and (c) for births with interventions [ 46 ]. Moreover, findings from the US found higher rates of mistreatment in hospital settings than in community birth settings such as birth centers and when women’s and providers’ preferences for care did not match one another [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past years more and more women opened up about instances of mistreatment in childbirth, such as physical or verbal abuse, discrimination, unconsented interventions, loss of autonomy, or informal coercion. The current state of research suggests that mistreatment of women in childbirth occurs regularly and is not limited globally to particular geographical areas [38,[44][45][46][47]. Spanning 34 countries, a systematic review from the World Health Organization highlighted that mistreatment can occur at the levels of interpersonal interaction and…”
Section: Plos Onementioning
confidence: 99%
“…Over the past years more and more women opened up about instances of mistreatment in childbirth, such as physical or verbal abuse, discrimination, unconsented interventions, loss of autonomy, or informal coercion. The current state of research suggests that mistreatment of women in childbirth occurs regularly and is not limited globally to particular geographical areas [38,[44][45][46][47]. Spanning 34 countries, a systematic review from the World Health Organization highlighted that mistreatment can occur at the levels of interpersonal interaction and…”
Section: Plos Onementioning
confidence: 99%